2023
DOI: 10.1109/access.2022.3232726
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Dynamic Resistance and Total Loss of HTS CORC Cables

Abstract: In some high temperature superconducting (HTS) applications, HTS coated conductors carry DC current under external AC magnetic fields. Dynamic resistance occurs when the amplitude of the magnetic field is greater than the threshold magnetic field of the coated conductors. The resulting AC loss, termed as total loss, consists of dynamic loss due to dynamic resistance and magnetization loss due to the shielding currents caused by the AC magnetic field. Conductor on round core (CORC) cables wound with HTS coated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…The mixed current vector potential-magnetic vector potential formulation, usually called T − A formulation [61], has been recently proposed and used to solve electromagnetic problems, including HTS tapes using the thin sheet approximation, such as stacks [25,26], coils [24,27,62], TST cables [27], and CORC cables [63,64]. In the T − A formulation, T is solved in the HTS domains (thin sheets) while A is solved everywhere else, with the advantage of having the A formulation solving domains with linear electromagnetic behaviour and leaving the HTS nonlinear model for the T−formulation.…”
Section: Mixed Current Vector Potential-magnetic Vector Potential (T ...mentioning
confidence: 99%
“…The mixed current vector potential-magnetic vector potential formulation, usually called T − A formulation [61], has been recently proposed and used to solve electromagnetic problems, including HTS tapes using the thin sheet approximation, such as stacks [25,26], coils [24,27,62], TST cables [27], and CORC cables [63,64]. In the T − A formulation, T is solved in the HTS domains (thin sheets) while A is solved everywhere else, with the advantage of having the A formulation solving domains with linear electromagnetic behaviour and leaving the HTS nonlinear model for the T−formulation.…”
Section: Mixed Current Vector Potential-magnetic Vector Potential (T ...mentioning
confidence: 99%
“…Terzioglu et al [31] respectively analyzed the AC loss characteristics of a single-layer CORC cable and a two-layer CORC cable and found that the transport AC loss of a single-layer CORC cable mainly comes from the eddy current loss generated by the axial magnetic field. Qiao et al [32] studied the dynamic resistance of single-layer and two-layer CORC cables. Wang et al [33] studied the magnetization loss of single-layer, two-layer and three-layer CORC cables, and concluded that the tape striation can significantly reduce the magnetization loss of CORC cables.…”
Section: Introductionmentioning
confidence: 99%
“…There are extensive reports on the dynamic resistance and voltage response when REBCO CCs carry DC currents under AC magnetic fields, regarding the dependence on the amplitude and frequency of AC magnetic fields [25][26][27][28][29][30][31][32][33][34][35][36], operating temperatures [27,30,35,37], DC currents [25-30, 35, 38, 39] and waveforms of AC magnetic fields [39]. Several reports also present research on the influence of DC magnetic fields on the dynamic resistance and voltage of the CCs [22][23][24].…”
Section: Introductionmentioning
confidence: 99%